Process analysis of department of management and real estate management of supermarket company - Vozáb, Václav; Oškrdal, Václav; Bürger, Michal; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2013)
This thesis deals with realization of process analysis of department of management and real estate managnement of a supermarket company. The goal of this work, addressed in the practical part, is to map the processes in terms of business process diagrams with description of these processes, identify potential inconsistencies and eventually recommend a revision of current documents. The theoretical part explains the concepts of process management, process, process analysis and procedure of mapping process. There are also described and evaluated basic methods and standards for process modeling.
Vedoucí práce: Václav Oškrdal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses